The Effect of Social Media Marketing and Word of Mouth on Consumer Purchase Interest in Culinary MSMEs in Jakarta Moderated Entrepreneurship Orientation - Kustiadi Basuki; Vinda Aulia (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of Social Media Marketing and Word of Mouth on consumer buying interest in culinary MSMEs in Jakarta moderated by Entrepreneurship orientation. The population in this study was 202 culinary MSME consumers in Jakarta, with purposive sampling as a sample using structural equation model (SEM) statistical test tools partial least squares (PLS) through SmartPLS software. Data collected by questionnaires that have been tested for validity and reliability. The results of this study are based on the first hypothesis, it was found that the relationship between Social Media Marketing on Buying Interest has a positive or significant effect on culinary SMEs in Jakarta. The results of the second hypothesis tester, it was found that the relationship between Word of Mouth and Buying Interest had a positive or significant effect on Djakarta culinary SMEs. The results of the third hypothesis, it was found that the relationship between Entrepreneurial Orientation and Purchase Interest had a positive or significant effect on culinary SMEs in Jakarta. The results of the fourth hypothesis, it was found that Social Media Marketing on Buying Interest was not able to be moderated by Entrepreneurship Orientation positively and significantly in culinary MSMEs in Jakarta, significant in culinary SMEs in Jakarta.